Mondhuk Entar Ngajhi Ben Ngabdhi - Arifin, Samsul; Fatah, Zaehol; Sari, Iin Puspita (Koordinatorat Perguruan Tinggi Keagamaan Islam Swasta Wilayah IV Surabaya, 2024)
Pesantren are growing rapidly and are among the most popular choices for learning to improve Islamic values in the digital era in maintaining social harmony. However, there has been no research on the reasons for walisantri in making decisions to choose pesantren as a place of learning for their children. This study aims to explain the motivational needs survey of walisantri (parents of students) in determining the choice of Salafiyah Syafi'iyah Situbondo pesantren in the perspective of McClelland's theory. The research method used a survey approach with cluster sampling of 613 people. The survey results showed a high score for the need for achievement of 4.69 or strongly agree and the need for belonging of 4.66 or strongly agree. This is consistent with the pesantren's slogan,